Aplikasi metabolit sekunder dari tiga isolat Pseudomonas fluorescens untuk mengendalikan penyakit antraknosa pada daun kakao - Fitrianti FITRIANTI; Loekas - SOESANTO; Endang MUGIASTUTI; Murti Wisnu Ragil SASTYAWAN; Abdul MANAN (INDONESIAN RESEARCH INSTITUTE FOR BIOTECHNOLOGY AND BIOINDUSTRY, 2022)
Anthracnose caused by Colletotrichum gloeosporoides is an important disease in cocoa. This research aimed to determine the effectiveness of secondary metabolites derived from three isolates of Pseudomonas fluorescens to control cocoa leaves anthracnose, and their influence on the growth of cocoa plants. The research was conducted at a smallholder cocoa plantation in Putat Village, Patuk District, Gunung Kidul Regency, Yogyakarta for four months. A randomized block design was used with four replicates and seven treatments consisted of control, application of secondary metabolites from P. fluorescens P60, P. fluorescens P20, P. fluorescens P8, combination P. fluorescens P60 + P20, P. fluorescens P60 + P8, and P. fluorescens P20 + P8. Variables observed were disease intensity, infection rate, number of healthy shoots and qualitative phenolic compound. Resultsof the research showed that the secondary metabolites of P. fluorescens P60, P20 and P8 alone or in combination suppressed the disease intensity by42.01-54.50%. The infection rate caused by metabolite secondary of P. fluorescens P60, P20, P8, P. fluorescens P60+P20, P. fluorescens P60+P8,and P. fluorescens P20+P8 was 0.23; 0.25; 0.26; 0.26; 0.31; and 0.24 units/day, respectively. The secondary metabolites of P. fluorescens P60 increased the number of healthy shoots by 67.44 %. The secondary metabolites of P. fluorescens P60 increased phenolic compounds (tannin, saponin, and glycosides) in cocoa leaves.[Keyword: leaves anthracnose, Colletotrichum gloeosporoides, cocoa, secondary metabolites, Pseudomonas fluorescens] AbstrakAntraknosa yang disebabkan oleh Colletotrichum gloeosporioides merupakan penyakit penting pada tanaman kakao. Penelitian bertujuan mengkaji keefektifan metabolit sekunder dari tiga isolat Pseudomonas fluorescens untuk mengendalikan penyakit antraknosa pada daun kakao, serta pengaruhnya terhadap pertumbuhan tanaman kakao. Penelitian dilaksanakan di perkebunan kakao rakyat, Desa Putat, Kecamatan Patuk, Kabupaten Gunung Kidul, Yogyakarta selama empat bulan. Penelitian menggunakan rancangan acak kelompok untuk menguji 7 perlakuan yang diulang 4 kali, perlakuan yang diuji adalah kontrol, aplikasi metabolit sekunder P. fluorescens P60, P. fluorescens P20, P. fluorescens P8, kombinasi P. fluorescens P60+P20, P. fluorescens P60+P8, dan P. fluorescens P20+P8. Variabel pengamatan meliputi intensitas penyakit, laju infeksi, jumlah tunas sehat, dan kandungan senyawa fenol secara kualitatif. Hasil penelitian menunjukkan bahwa perlakuan metabolit sekunder P. fluorescens P60, P20, dan P8 secara tunggal dan gabungan mampu menekan intensitas penyakit berkisar 42,01-54,50%. Laju infeksi perlakuan metabolit sekunder P. fluorescens P60, P. fluorescens P20, P. fluorescens P8, kombinasi P. fluorescens P60+P20, P. fluorescens P60+P8 dan P. fluorescens P20+P8 berturut-turut 0,23; 0,25; 0,26; 0,26; 0,31; dan 0,24 unit/hari. Metabolit sekunder P. fluorescens P60 meningkatkan jumlah tunas sehat sebesar 67,44%. Perlakuan P. fluorescens P60 meningkatkan senyawa fenol (saponin, tanin, dan glikosida) pada daun kakao.[Kata kunci: antraknosa daun, Colletotrichum gloeosporoides, kakao, metabolit sekunder, Pseudomonas fluorescens]